Predictive immune markers in advanced melanoma patients treated with ipilimumab - Umansky, Viktor; Utikal, Jochen; Gebhardt, Christoffer (OncoImmunology, 2016)
Myeloid-derived suppressor cells (MDSCs) and chronic inflammatory factors induce immunosuppression and disease progression in advanced melanoma patients. They could serve as important markers allowing the identification of patients with high risk of melanoma progression as well as the detection of those patients who may benefit from the therapy with ipilimumab.
Gesehen am 24.10.2019